PENGARUH PREOCCUPIED ATTACHMENT DAN AUTHORITARIAN PARENTING STYLE TERHADAP SELF-ESTEEM PADA REMAJA SMA DI SURABAYA - Ersa Lanang Sanjaya; Maghrizkia Aulia Wilda (EXPERIENTIA : Jurnal Psikologi Indonesia, 2021)
This study aimed to determine the effect of Preoccupied Attachment Style and Authoritarian Parenting Style on Self-Esteem in high school adolescents in Surabaya. This research was conducted with a correlational quantitative design. The subjects of this study were 121 high school students in Surabaya. The sampling technique used is non-probability incidental sampling with the Slovin formula. Retrieval of data using the State Self Esteem Scale (Heatherton & Polivy, 1991), Attachment Style Scale (Bartholomew & Horowitz, 1991), Parental Authority (Buri, 1991). These three scales were adapted to Indonesian. Data analysis in this study used simple regression analysis with JASP version 9.2 software. The results of the regression test showed that when tested together, preoccupied attachment and authoritarian parenting style had a significant effect on adolescent self-esteem, but if we examined the relationship between each variable, preoccupied attachment had a negative effect on self-esteem, while authoritarian parenting style had no effect on self-esteem.Keywords: preoccupied attachment, authoritarian parenting, self-esteem